Engagements et circulation des artistes au xviiie siècle. Le cas des théâtres Alibert et Argentina de Rome - Élodie Oriol (Diasporas: Circulations, Migrations, Histoire)
This article investigates the forces that drove mobility among artists in 18th Century Rome, which was then a major European music capital. During this period, artists (composers, singers, dancers and instrumentalists) gathered in the pontifical city every year to take part in the operatic season during Carnevale and, by doing so, subjected themselves to criticism from large and impatient audiences. More specifically, this work analyzes the manner in which artists were recruited in Rome’s Alibert and Argentina theatres. Their archival sources present a rich account of the behind-the-scenes activities (contracts, correspondence, deliberations) that took place at these two theatrical institutions. These allow one to discern the inner workings of the theatre season and to bring artists’ mobility to light. The work covers the negotiations among the different players of the theatre world (theatre managers, artists, mediators) and will focus especially on the choices made by theatre managers with respect to artists’ appointments.